EFFECT OF SUPPLEMENTATION OF PROBIOTICS AND MULTIENZYMES IN LOW ENERGY DIET ON THE PERFORMANCE OF JAPANESE QUAILS - Panchbuddhe, A N; Zanzad, A A; Ramteke, B N; Lanjewar, R D; Patankar , R B (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
An experiment was conducted to study the effect of supplementation of probiotics and multienzymes in low energy diet in Japanese quails from day old to forty-two days. The dietary treatment consisted of four groups viz., Control ( T0 ) fed on standard quail diet . Group T1 fed low energy diet , group T2 fed low energy diet along with multienzymes @ 500mg/kg and Group T3 fed with low energy diet along with probiotics (Lactobacillus sporogenes) @ 500mg/kg. All the groups were on isonitrogenous diets and were reared under standard managemental conditions. Metabolic trial was conducted for nitrogen balance. It was observed that there was significant (P
Keywords: quail; low energy diet; probiotics; multienzymes